A Brief on Optical-based Investigation towards The Interfacial Behaviors during High Viscous Liquid/Gas Countercurrent Two-Phase Flow in a Complex Conduit Representing 1/30 Down-Scaled of PWR Hot Leg Geometry - Achilleus Hermawan Astyanto; Indarto Indarto; Deendarlianto Deendarlianto (International Journal of Applied Sciences and Smart Technologies, 2023)
The present work briefly investigates liquid/gas countercurrent two-phase flow phenomena which can be specifically found in a mitigation during an accidental scenario in the operation of a nuclear reactor. A comprehensive knowledge on the corresponding phenomena is obviously important to avoid the failure on the cooling mechanism. Here, a pair of fluid containing high viscous liquid/gas flows through a complex conduit representing 1/30 scaled-down of PWR hot leg’s typical geometry. Furthermore, the flow structures were visually observed, while the film thicknesses are extracted by an image processing algorithm through the corresponding optical-tabulated data. The obtained results reveal that a rather sharp decrease in liquid film corresponds to the flow regime transition.Keywords: Countercurrent two-phase flow, liquid film thickness, high viscous liquid, complex conduit